Digital marketing as an effective tool for business promotion - Koval, A. Yu. (ТДАТУ, 2021)
Digital marketing is an up-to-date, universal, effective way to promote goods, services, brands. It is a new trend in global marketing that actively and rapidly relegating traditional advertising to the background.
Keywords: work information; digital marketing